2019
DOI: 10.1002/gea.21726
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing human–landscape interactions in the context of ancient iron smelting on Elba Island, Italy, using sedimentological evidence

Abstract: We reconstruct human–landscape interactions in the context of ancient bloomery smelting on Elba Island, Tyrrhenian Sea, based on sedimentological evidence. Elba was, together with Populonia, the center of iron production in antiquity (mid‐6th century B.C.E. to 1st century C.E.). The sediment sequences obtained by vibracoring in the Campo plain reveal that the Holocene transgression triggered aggradation during the Early–Middle Holocene (>5.4 ka cal BP). Nevertheless, wetland conditions prevailed in low‐lying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Second, information from (limited) pollen data indicates a shift in the species composition—from deciduous oak to woody shrubland species (Ericaceae) —rather than a loss of woodland cover. Erica arborea and Arbutus were common fuelwood species in Etruscan and Roman metallurgy [ 61 , 86 ]. Sedimentological analysis of alluvial sediments have shown that morphodynamics—i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, information from (limited) pollen data indicates a shift in the species composition—from deciduous oak to woody shrubland species (Ericaceae) —rather than a loss of woodland cover. Erica arborea and Arbutus were common fuelwood species in Etruscan and Roman metallurgy [ 61 , 86 ]. Sedimentological analysis of alluvial sediments have shown that morphodynamics—i.e.…”
Section: Discussionmentioning
confidence: 99%
“…the deposition of high-magnitude flood layers, slope deposits, and gravel—in the Campo plain (central Elba) increased during the Roman smelting period. Nevertheless, there is no distinct evidence of island-wide clear-cutting [ 61 ]. Reasons other than fuelwood scarcity—such as upheaval in the Roman world between the Republic and the Empire—might have fostered the abandonment of smelting sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations